Ethnobotanical Investigation of Medicinal Plants and their Importance, Traded in the Public Herbal Markets and Centers of Gaza Strip, Palestine - Mohamad Abou Auda; Tarek Elbashiti; Samar Alghuff (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
A comprehensive assessment of medicinal plant variety used in folk treatment in Gaza was conducted in order to discover medicinal plants still in use by therapists and their relevance in health care. By interviewing 20 informants from various places, an ethnobotanical survey was undertaken to examine and document plant species utilized in traditional medicine. The research identified 72 different medicinal pqlant species belonging to 33 different families. Plant components that were most commonly used were leaves (41%), stems (18%), and seeds (14%). The most common ailments treated were gastrointestinal, circulatory, and urinary system issues.